2006
DOI: 10.1002/ijc.21814
|View full text |Cite
|
Sign up to set email alerts
|

Regular aspirin use and esophageal cancer risk

Abstract: Given the high mortality rate and the rapidly increasing incidence rate of esophageal carcinoma, chemopreventive agents are highly desirable. Aspirin has been shown to be associated with reduced risk of developing colorectal carcinoma and other cancers. Even though previous studies have shown reduced risk of esophageal cancer associated with aspirin use, results were inconsistent with respect to frequency and duration of use. In this hospital-based case-control study, 163 esophageal cancer cases were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
0
27
1
Order By: Relevance
“…Among those studies that have examined the association between aspirin or NSAID and risk of esophageal cancer, all but two (7,57) have reported 30% to 50% lower risks of esophageal cancers among people who used NSAIDs compared with never users (44,45,(58)(59)(60)(61)(62). We are aware of only one previous study that has separately measured associations for adenocarcinomas of the esophagus and esophagogastric junction (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those studies that have examined the association between aspirin or NSAID and risk of esophageal cancer, all but two (7,57) have reported 30% to 50% lower risks of esophageal cancers among people who used NSAIDs compared with never users (44,45,(58)(59)(60)(61)(62). We are aware of only one previous study that has separately measured associations for adenocarcinomas of the esophagus and esophagogastric junction (45).…”
Section: Discussionmentioning
confidence: 99%
“…Of two studies that have assessed the duration of NSAIDs intake and risk of esophageal adenocarcinoma (10,45), neither observed any association between duration and risk of adenocarcinoma. From five studies that evaluated association between exposure to NSAIDs and risk for any type of esophageal cancer (10,45,47,(58)(59)(60)(61)63), three reported lower risks among people with longer exposure to NSAIDs (59,60,63). The remaining studies had smaller numbers of participants with wide confidence intervals in the longer duration categories, masking possible associations.…”
Section: Discussionmentioning
confidence: 99%
“…We limited our analysis to papers reporting case -control or cohort studies of the association between the use of either aspirin or non-aspirin NSAIDS and the risk of oesophageal or gastric adenocarcinomas. We included the following studies for the oesophagus (Farrow et al, 1998;Cheng et al, 2000;Lindblad et al, 2005;Anderson et al, 2006;Jayaprakash et al, 2006;Ranka et al, 2006;Fortuny et al, 2007;Duan et al, 2008;Sadeghi et al, 2008), cardia (Farrow et al, 1998;Zaridze et al, 1999;Akre et al, 2001;Fortuny et al, 2007;Duan et al, 2008;Sadeghi et al, 2008), non-cardia (Farrow et al, 1998;Zaridze et al, 1999;Akre et al, 2001;Fortuny et al, 2007;Duan et al, 2008), and gastric NOS (Thun et al, 1993;Schreinemachers and Everson, 1994;Coogan et al, 2000;Langman et al, 2000;Akre et al, 2001;Sorensen et al, 2003;Ratnasinghe et al, 2004;Lindblad et al, 2005) and excluded a few studies from certain sections that did not specify the agent (Garidou et al, 1996;Suleiman et al, 2000) or the histology of the oesophageal tumours (Funkhouser and Sharp, 1995;Langman et al, 2000). Two other studies, one prospective and one retrospective, reported on the association between aspirin and oesophageal adenocarcinoma, but included only subjects with Barrett's oesophagus in the reference group (Tsibouris et al, 2004;Vaughan et al, 2005) and these pap...…”
Section: Meta-analysismentioning
confidence: 99%
“…Given at low dose, gastrointestinal toxicity could be minimized by the co-administration of a proton pump inhibitor [8]. Aspirin use has been reported to confer protection against esophageal cancer, showing a 50 % reduction in risk of esophageal carcinoma [9,10]. So far, most evidence on the antitumor effect of aspirin relates to use in prevention rather than treatment.…”
Section: Introductionmentioning
confidence: 97%